Men teaching pre-school children: Non-traditional career choice among pre-service male teachers - Md Arshad, Syimamarsni; Abd Karim, Aishah Hanim; Anuar, Zubaidah; Musazay, Asma (IWNEST Publication, 2015)
Background: Teaching early childhood children was often considered as a female job as it involved nurturing. The emergence of 11.8% male teachers teaching pre-school children in Malaysia and arising number of male students studying early-childhood education required a specific study on the issue. The participants in this study were preservice male teachers, studying a degree program at the International Islamic College (IIC) and had undergone their practical teaching at pre-schools. The method of this study was a qualitative study, which involved case studies and in-depth interviews. Two participants were selected by using purposeful sampling. The data analysis applied traditional methods which include coding and recoding, and the data gained were categorized and arranged according to the generated themes. Objective: The objective of the study is to investigate what makes the male students choose this non-traditional career, their beliefs about this career and advantages and disadvantages that they experienced on being pre-service male teachers. Results: The results of this study included factors that influence pre-service male teachers in becoming pre-school teachers, their perceptions about male teachers teaching pre-school children as well as advantages and disadvantages that they had experienced. Conclusion: In conclusion, this study highlighted the factors that influence two pre-service male early childhood teachers to study this field as well as their beliefs about the female-dominated industry. In addition to that, it also discussed the challenges faced throughout their journey in becoming pre-school teachers.